Dialectics of the Qur’an through Q 2:258 - Belhaj, Abdessamad (Islamic Studies, 2012)
This article explores the dialectics of the Qur’an through the exegesis of Q 2:258. Above all, it investigates the Qur’┐nic debate in the framework of the literary debate, munazarah. First, I examine the terms and ethics of the Qur’anic dialectics. Subsequently, the argumentative sequence of an Abrahamic debate as related in Q 2:258 will be analyzed. The evolution of interpretations endorsed by exegetes reveals the gradual infiltration of theological/juridical dialectics into the reading of the Qur’anic debate.